Sharia-Oriented Financial Management in Islamic Boarding Schools - Dermawan, Oki; Kusuma Yusuf, Trisna; Defriyanto, Defriyanto; Busmayaril, Busmayaril; Segu, Segu (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Islamic boarding schools (pesantren) play a pivotal role in Islamic education, requiring sound and Sharia-compliant financial management to ensure institutional sustainability. Nevertheless, prior studies on pesantren financial governance remain fragmented and largely descriptive, providing limited integrative insight into Sharia-oriented managerial frameworks. This study aims to systematically review and synthesize existing literature on Sharia-based financial management in pesantren by identifying dominant principles, management components, implementation models, and governance challenges. Employing a Systematic Literature Review (SLR), peer-reviewed articles were retrieved from reputable academic databases using predefined inclusion and exclusion criteria and analyzed through thematic synthesis. The results indicate that Sharia-oriented financial management in pesantren is consistently grounded in the principles of amanah (accountability), shafafiyyah (transparency), ‘adl (justice), and Islamic ethical compliance. Core components include financial planning and budgeting, fund mobilization, Sharia-based financial reporting, and internal control mechanisms. However, recurring challenges persist, notably limited managerial competence, weak financial standardization, and insufficient integration of Sharia accounting frameworks. This study contributes theoretically by developing an integrative conceptual map of Sharia-oriented financial governance in pesantren, addressing gaps in prior isolated studies. Practically, the findings inform pesantren leaders and policymakers in designing standardized financial systems, capacity-building programs, and regulatory frameworks to strengthen Sharia-compliant financial governance.